Uma dupla vida de risco: reflexões sobre o trabalho paralelo (bico) na Polícia Militar do Pará - LIMA, Roseane Magalhães (Universidade Federal do Pará, 2014)
The beak or parallel work is some of the most common practices among the military policemen; it is exercised by them: in parties, events and safety of natural persons. Although it is the warranty of an extra income, however, that propitiates that the policeman becomes a person without leisure and always absentee of the family. Position that, we informed that in this work have for objective to show as the nets of the beak are structured among the policemen, which create a true organization of work sale that, for that, they are used of the status quo or of the police power for us to guarantee the private safety. We will also show how they happen the days of parallel work and their risks, as well as the consequences of his/her informality. Besides, we will present the intrigues of these organizations, his/her structure, his/her hierarchy and like her it operates, where we verified that there is an inversion of the hierarchical values of the military organization.